Regional differences in temporomandibular joint inflammation in patients with juvenile idiopathic arthritis: a dynamic post-contrast magnetic resonance imaging study. Issue 9 (September 2020) - Buch, K.; Peacock, Z.S.; Resnick, C.M.; Rothermel, H.; Kaban, L.B.; Caruso, P.
Abstract: The purpose was to determine whether there are regional differences in temporomandibular joint (TMJ) inflammation in patients with juvenile idiopathic arthritis (JIA). This was a retrospective study of all patients with dynamic, contrast-enhanced magnetic resonance imaging through the TMJs at Massachusetts General Hospital between January 2015 and July 2016. The patient cohort included those with a history of JIA and control patients who underwent MRI for other routine clinical purposes. TMJ inflammation was quantified as the difference between post-gadolinium and pre-gadolinium articular T1 signal intensity normalized to post-gadolinium signal intensity of the longus capitis muscle. TMJ enhancement profiles were generated for the lateral, central, and medial portions of the TMJ. Regional differences in TMJ enhancement were investigated using basic descriptive statistics. Medial edge enhancement of the TMJs was highest in symptomatic JIA joints, followed by asymptomatic JIA, then control joints. Medial edge enhancement was a significant discriminator between symptomatic JIA TMJs and control joints ( P = 0.0001), between symptomatic and asymptomatic JIA TMJs ( P = 0.0003), and between asymptomatic JIA TMJs and controls ( P = 0.0019). A shift in distribution of TMJ enhancement towards the medial edge that was seen uniquely in both asymptomatic and symptomatic JIA TMJs compared to control joints was found. This suggests a pattern of worsening medial edge inflammation with disease.